If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a = -1e + -1s + -1y Solving a = -1e + -1s + -1y Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Simplifying a = -1e + -1s + -1y
| w^2-13w+42.25=0 | | 1/4x^4-9/25=0 | | ydx=x(lnx-lny)dy | | 5x=(3x-3)(m+4) | | 0.90n=n+15 | | -17+8x=14 | | 0.75p=18 | | 8x-4x+5=x-5+10 | | 2x+40=9x-2 | | 0=1/3x=1 | | 11r+60=15 | | 8(v+3)-2v=3(2v+4)-18 | | 3(x-8)=x+2 | | a=cx+bc | | 11x-12=5(2x+3)-3 | | 6/27 | | 0.06t+0.09(t+500)=150 | | 2x+17=9x-4 | | 2(t-3)-5(5t-6)=9-6(7t-5) | | 16(1/2)= | | 9m^5-18m^3-12m^2+81= | | 5x+10=3+24 | | X-2/3y=1/4 | | 8x^3-20x^2+6x-15=0 | | 4[1-(-2x-2)]=72x+76 | | 2x-4=14-x | | 12x-5=10x+7 | | 9+11=711 | | p=y+s-1 | | 2x/3-4=x/6-3/2 | | 4x+6-2(x+1)=8x+9 | | 11x+5=13x-7 |